1996
DOI: 10.1007/bf00290519
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of morphometric changes in murine experimental osteoarthritis using image analysis

Abstract: The aim of this study was to evaluate a method for the quantification of cartilage erosions and osteophyte sizes in a murine model of osteoarthritis (OA). Mice in which OA was induced in the knee joint by intra-articular injection of bacterial collagenase were used. With an interactive image analysis system, the areas occupied by osteophytes and the areas of erosions of the articular cartilage were measured on histological sections by two independent observers at two time points. Measurements of osteophyte are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Joints were embedded intact into paraffin with the patella down and the femur and tibia forming equal angles to the rim of the embedding cassette, ensuring that the joint was not rotated medially or laterally. Joints were then serially sectioned in a coronal plane, and 4 to 5 representative midcoronal 4-μm-thick sections that spanned approximately 100 μm were selected and stained as previously described 15 with hematoxylin & eosin (H&E) and Safranin-O.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Joints were embedded intact into paraffin with the patella down and the femur and tibia forming equal angles to the rim of the embedding cassette, ensuring that the joint was not rotated medially or laterally. Joints were then serially sectioned in a coronal plane, and 4 to 5 representative midcoronal 4-μm-thick sections that spanned approximately 100 μm were selected and stained as previously described 15 with hematoxylin & eosin (H&E) and Safranin-O.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study developed a method to quantitate histological changes in murine stifle joints using image analysis on a single midcoronal section per joint and found that measurements of articular cartilage degradation and osteophyte size were reproducible. 15 Cellular parameters (e.g., chondrocyte numbers) and changes in subchondral bone were not evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…It appeared to be possible with this method to measure the amount of cartilage loss in the medial and lateral tibial plateau reproducibly. Unfortunately, cartilage damage of the femoral condyle could not be measured with sufficient reproducibility [12].…”
Section: Quantification Proceduresmentioning
confidence: 99%
“…The amount of cartilage loss and the size of the osteophytes were quantified using a previously developed and validated method [ 12]. In short, the amount of cartilage loss was presented as a percentage of the total cartilage area in that compartment.…”
Section: Quantification Proceduresmentioning
confidence: 99%